In Vivo Brain Deformation in a Sheep Model of Rapid Head Rotation - Charlie Cenin Magarey; Mark Plummer; Peter Alec Cripton; Claire Frances Jones (Annals of Biomedical Engineering, 2026)
Purpose Synchronous measures of head kinematics and in vivo brain deformation during rapid head rotation are needed to advance understanding of traumatic brain injury (TBI) mechanics and enhance computational modeling as a tool for injury risk assessment and prevention. The aims of this study were to produce repeatable rapid rotation of the in vivo sheep head, to assess the viability of the sonomicrometry method for measuring multipoint brain displacement, and to quantify the in vivo brain deformation response to rapid rotation. Methods In three anaesthetized adult sheep, arrays of sonomicrometry transceivers were implanted into the brain and rigidly attached to the inner skull surface. Repeatable, rapid, sagittal plane head rotation (nominally about the second cervical vertebra) was induced with a non-impact head rotation apparatus. Computed tomography imaging was performed to assess relative motion between transceivers and brain tissue. Three-dimensional brain displacement, strain, and head kinematics were assessed for repeatability. Results The location of up to 13 (mean = 11) brain transceivers were tracked in each of 11 rapid head rotation tests. Peak head angular acceleration and velocity were up to 38.56 krad/s 2 and 30.43 rad/s, respectively, and average duration of head motion was 241.9 ± 23.1 ms. Pre-to-post-test transceiver displacement in brain tissue was less than the spatial resolution of the measurement system, and brain displacements measured during rapid head rotation had excellent repeatability (CORA score 0.99). Brain displacements and strains up to 2.47 mm and 18%, respectively, were observed. The brain exhibited decaying sinusoidal rotational deformation in the sagittal plane with oscillating tension-compression waves. Conclusion Sonomicrometry was reliably applied in vivo and provided repeatable measurements of brain deformation in a non-survival large animal model of rapid head rotation.

Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - John Thompson; Mark A. Weaver; Ingrid Lupatsch; Robin J. Shields; Sue Plummer; Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be an approach for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio ( Listonella ) anguillarum , Vibrio alginolyticus , and V. harveyi , using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum , and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (> 100°C) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH; however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp ( Penaeus vannamei)— identified tentatively as Carnobacterium maltaromaticum . This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and reduced shrimp survival at a dose of 1 × 10 7 bacteria/shrimp. During a 28-day feeding trial, juvenile P. vannamei fed with L. plantarum supplemented diets showed no gross changes in growth parameters compared with the control. We suggest that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Capturing Energy from the Motion of the Ocean in a Crowded Sea - Mark L. Plummer; Blake E. Feist (Coastal Management, 2016)

A Framework for Exploring the Role of Bioeconomics on Observed Fishing Patterns and Ecosystem Dynamics - John Wiedenmann; James Wilen; Phillip Levin; Mark Plummer; Marc Mangel (Coastal Management, 2016)

Conceptualization of Social-Ecological Systems of the California Current: An Examination of Interdisciplinary Science Supporting Ecosystem-Based Management - Phillip S. Levin; Sara J. Breslow; Chris J. Harvey; Karma C. Norman; Melissa R. Poe; Gregory D. Williams; Mark L. Plummer (Coastal Management, 2016)

The Role of Eelgrass in Marine Community Interactions and Ecosystem Services: Results from Ecosystem-Scale Food Web Models - Mark L. Plummer; Chris J. Harvey; Leif E. Anderson; Anne D. Guerry; Mary H. Ruckelshaus (Ecosystems, 2013)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

Sequence and peptide-binding motif for a variant of HLA-A*0214 (A*02142) in an HIV-1-resistant individual from the Nairobi Sex Worker cohort - Mark Luscher; Kelly MacDonald; Job Bwayo; Francis Plummer; Brian Barber (Immunogenetics, 2001)

Sequence and peptide-binding motif for a variant of HLA-A*0214 (A*02142) in an HIV-1-resistant individual from the Nairobi Sex Worker cohort - Mark A. Luscher; Kelly S. MacDonald; Job J. Bwayo; Francis A. Plummer; Brian H. Barber (Immunogenetics, 2001)